The Annals of the Poor - Richmond, Legh, 1772-1827 (Salt Lake City, UT : Project Gutenberg, 2006)
"The Annals of the Poor" by Legh Richmond is a religious narrative likely written in the early 19th century. This work provides a moving account of the lives of the impoverished, showcasing their spiritual journeys and the grace of God as seen in their everyday struggles. The central character introduced is Elizabeth, the Dairyman's daughter, who undergoes a profound transformation from a life of worldly pleasures to one devoutly centered on her faith. The opening of the book sets the stage for Elizabeth's journey towards spiritual enlightenment, which is exemplified through a heartfelt letter she writes to the Reverend Richmond. The letter illustrates her deep concern for the salvation of others, particularly her sister, who has just passed away. Through her words, readers gain insight into her humble yet fervent devotion and her desire for a life committed to serving God. The narrative also includes the poignant reflections of Elizabeth's father, highlighting the stark contrast between the spiritual richness found among the poor compared to worldly riches. As the story unfolds, it promises to explore themes of faith, providence, and the redemptive power of grace amidst hardship. (This is an automatically generated summary.)
The dairyman's daughter -- The negro servant -- The young cottager -- The cottage conversation -- A visit to the infirmary.
Release date is 2006-10-30
Transcribed from the 1900 T. Nelson and Sons edition by David Price
Keywords: Christian life -- Juvenile fiction; Poor -- Juvenile fiction; Conduct of life -- Juvenile fiction; Children's stories